INHALED CORTICOSTEROID PHOBIA AMONG PARENTS OF ASTHMATIC CHILDREN (Journal of Medical & Health Sciences Review, 2025)
Introduction: Inhaled corticosteroids are crucial in managing childhood asthma, reducing inflammation, and preventing exacerbations. However, parental ICS phobia, fueled by growth concerns, weakens immunity, and dependency fears hinder adherence and asthma control. This study aims to gauge ICS phobia prevalence among parents of asthmatic children and pinpoint related factors.Methodology: This study conducted at CMH, Muzaffarabad from June to November 2024 included 168 parents of children aged 2–10 years with asthma using ICS therapy. Information on demographics, ICS adherence, parental concerns, and asthma control was collected through a structured questionnaire. ICS phobia was identified based on misconceptions, adherence, and alternative treatment preferences. Data were analyzed using SPSS version 26, with statistical significance at p